2019
DOI: 10.1038/s41598-019-56915-9
|View full text |Cite
|
Sign up to set email alerts
|

A metrological approach to the analysis of choroidal thickness by optical coherence tomography 3D scans in myopia research

Abstract: In myopia research, changes of choroidal thickness in response to optically induced signals serve as predictor for changes in axial length that might be correlated with myopia progression. Optical coherence tomography (OCT) provides a tool for imaging the choroid, however, with certain difficulties because of a limited visibility of the scleral-choroidal interface. Considering the previously reported effect sizes of thickness change in human myopia research, this study investigated the repeatability of automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…4 Bland-Altman plot demonstrating the agreement between Triton DRI-OCT and PLEX Elite 9000 for choroidal thickness measurements. a all subjects; b, c Subjects with axial length less than and more than 26 mm, respectively; d, e Subjects with choroidal thickness less than and more than 300 μm, respectively (Supplementary Table 1), consistent with several other studies [47][48][49][50][51][52][53][54]. This may be explained by the choroid's watershed zone, which is located between the optic disc and the fovea [55,56].…”
Section: Discussionsupporting
confidence: 87%
“…4 Bland-Altman plot demonstrating the agreement between Triton DRI-OCT and PLEX Elite 9000 for choroidal thickness measurements. a all subjects; b, c Subjects with axial length less than and more than 26 mm, respectively; d, e Subjects with choroidal thickness less than and more than 300 μm, respectively (Supplementary Table 1), consistent with several other studies [47][48][49][50][51][52][53][54]. This may be explained by the choroid's watershed zone, which is located between the optic disc and the fovea [55,56].…”
Section: Discussionsupporting
confidence: 87%
“… 54 Moreover, another methodologically similar study found the opposite for spectral-domain OCT scans, with the best repeatability in the nasal sectors due to thinner choroids and thus advantageous imaging properties. 42 However, comparisons to other past literature are limited, since the range of methodologies used and analyses reported are broad. In contrast to ChT, repeatability of CVI measurements did not show any regional variations, surprisingly not even in the extended nasal subfield.…”
Section: Discussionmentioning
confidence: 99%
“… 40 The coefficient of repeatability (CR) from nonnormal data was derived for each ETDRS region as explained elsewhere. 41 , 42 In short, the median of each of the three measurements per day and its difference to the overall mean across the 3 days were calculated. Subsequently, the resulting deltas were evaluated in a cumulative distribution function.…”
Section: Methodsmentioning
confidence: 99%
“…It plays an important role in various vision deteriorating diseases such as age related macular degeneration, choroidal neo-vascularization, central serous chorioretinopathy and chorioretinal atrophy in high myopia. 1,2 Choroidal thickness is determined by amount of vascularization and varies by age, sex, refractive state of eye along with any previous history of ocular trauma or surgery like cataract extraction. [3][4][5] Phacoemulsification is most common invasive intraocular surgery for removal of cataract and improves visual outcome markedly.…”
Section: Introductionmentioning
confidence: 99%